Benefits, Barriers and Solutions of Knowledge Management - Fikry, Amily (INTI Publishing House Sdn Bhd, 2005)
While the main objectives of knowledge management are Lo safeguard an organization’s intellectual capital and protect employees’ intellectual property, the effort of capturing knowledge will in turn ensure that valuable information is transferred and used by another worker at the right time, resulting in the increase of employees’ independence, innovativeness, performance and productivity. These will then be translated in terms of increase in sales, revenue and shareholder value. However, there are barriers to knowledge management. Knowledge management requires change and expertise. Change has to be implemented within allowable time and cost constraints. Encouraging employees to share their knowledge with others requires incentives. The use of technological and psychological aids would help ensure the effectiveness of knowledge management practices.